RELIABILITY OF SYSTEM THE CONSTRUCTION – THE BASIS AT RANDOM SEISMIC INFLUENCE, NORMALIZED ON 8 POINTS - Марина Сергеевна Дударева (Sovremennoe Stroitelʹstvo i Arhitektura, 2018)
In article the problem of probabilistic calculation of 9 floor reinforced concrete building located on the soil base with random parameters is considered. The problem is solved by method of statistical tests at which а number of numerical tests of system the construction – the basis at action earthquake is carried out. As settlement seismic influence set synthesized three-component accelerogram is accepted. Impact is presented in the form of non-stationary random process. Probabilistic parameters of the law of distribution of intensity of tension in soil are defined. On the obtained data quantitative assessment of reliability of system is made.